2005
DOI: 10.1083/jcb.200412162
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylinositol-4,5-bisphosphate hydrolysis directs actin remodeling during phagocytosis

Abstract: The Rho GTPases play a critical role in initiating actin polymerization during phagocytosis. In contrast, the factors directing the disassembly of F-actin required for fission of the phagocytic vacuole are ill defined. We used fluorescent chimeric proteins to monitor the dynamics of association of actin and active Cdc42 and Rac1 with the forming phagosome. Although actin was found to disappear from the base of the forming phagosome before sealing was complete, Rac1/Cdc42 activity persisted, suggesting that ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
268
1
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 235 publications
(289 citation statements)
references
References 49 publications
15
268
1
3
Order By: Relevance
“…[21][22][23] In agreement with previous observations, 34 we observed that such probe almost exclusively localizes at the plasma membrane where it distributes in discrete microdomains partially colocalizing with lipid rafts (R.G., unpublished data, December 2005). The interaction of NK cells with target cells was followed by a rapid consumption of PIP2 in the area of cytolytic synapse, whereas in contact-free membrane areas or in noncytolytic interactions we did not observe major PIP2 variations, thus ruling out rapid membrane turnover as the process responsible for the localized loss of membrane-associated GFP-PH probe.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…[21][22][23] In agreement with previous observations, 34 we observed that such probe almost exclusively localizes at the plasma membrane where it distributes in discrete microdomains partially colocalizing with lipid rafts (R.G., unpublished data, December 2005). The interaction of NK cells with target cells was followed by a rapid consumption of PIP2 in the area of cytolytic synapse, whereas in contact-free membrane areas or in noncytolytic interactions we did not observe major PIP2 variations, thus ruling out rapid membrane turnover as the process responsible for the localized loss of membrane-associated GFP-PH probe.…”
Section: Discussionsupporting
confidence: 80%
“…[21][22][23] By means of lentiviral-driven expression, we obtained high transduction efficiency without affecting NK-cell phenotype and functional properties. 25 As illustrated in Figure 1A, in isolated NK cells GFP-PH distributed throughout the plasma membrane where it localized in discrete microdomains; as expected, control GFP distributed homogeneously within the cell ( Figure 1B).…”
Section: Pip2 Dynamics During the Activation Of Nk Cytolytic Machinerymentioning
confidence: 99%
See 2 more Smart Citations
“…Actin polymerization drives phagosome formation, and in other phagocytic cell types it has been reported that F-actin begins to depolymerize at or before the point at which phagosome closure is complete (May and Machesky, 2001). It has been proposed that phosphatidylinositol 4,5-bisphosphate (PtdIns4,5P 2 ) at the site of formation of the phagocytic cup and its subsequent hydrolysis as the cup closes are the key signaling events regulating the cycle of actin polymerization and depolymerization (Botelho et al, 2000;Scott et al, 2005). Because anx A2 is a potent regulator of actin dynamics (Merrifield et al, 2001;Hayes et al, 2006) and binds both cholesterol-rich membranes, Ca 2ϩ , and PtdIns4,5P 2 Rescher et al, 2004;Gerke et al, 2005), it is well placed to function as a sensor of these second messengers and signaling intermediates, linking .…”
Section: Discussionmentioning
confidence: 99%